Sauna use as an activity leading to a reduction in modifiable risk factors for the development of hypertension - a systematic review - Adrian Hunek; Mateusz Góra; Anna Maria Bigdoń; Maciej Ćwiek; Przemysław Gorczyca; Patryk Sydor; Rafał Kreft; Aleksander Woźniak; Marcel Wartacz; Martyna Kozłowska (Kazimierz Wielki University, 2023)
Background: Hypertension prevalence is disturbingly increasing all over the world. Clinicians and patients are looking for new pharmacological as well as non-pharmacological methods to help fight too-high blood pressure.    Aim of this study:  The aim of this study is to present the current scientific literature on the potential that sauna bathing may help lower blood pressure, but additional data are needed to confirm these findings.   Material and methods:  A systematic review of the scientific and medical literature from the PubMed and Google Scholar databases was carried out. This was achieved according to the keywords: hypertension, sauna and sauna bathing. Items of literature were qualified for analysis.    State of knowledge:  Using the sauna is a pleasant way to spend time, and additionally it can have an impact on lowering blood pressure. During a sauna session, the superficial vessels dilate, which leads to a short-term decrease in blood pressure. And long-term, more frequent sauna use leads to a reduced risk of hypertension. Using the sauna enhances the effect of pharmacotherapy and non-pharmacological methods of fighting hypertension, such as physical activity and a healthy, balanced diet. Most of the research on the above topic was conducted in Finland, where its use has a centuries-old tradition.  Summary:  Using the sauna has an impact on lowering blood pressure values, thanks to which it can support the treatment of hypertension. Sauna use may be an interesting way to lower blood pressure values in physically disabled people. More studies conducted on larger groups of patients and the influence of other factors on blood pressure values are needed to make more accurate recommendations.